2022
DOI: 10.1002/anie.202209201
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Overlooked Photochemical Decomposition of Atmospheric Surface Nitrates Triggered by Visible Light

Abstract: The nitrogen oxides (NOx) formed by photochemical reaction of surface nitrates raise significant concerns. However, little is known about the effect of visible light (>380 nm) on nitrate decomposition and the reaction mechanism. Herein, the decomposition of surface nitrates is investigated under visible light. The results indicate that visible light photocatalysis contributes significantly to nitrate decomposition. Monodentate nitrate (m‐NO3−) can be decomposed into NOx by photogenerated electrons starting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…However, electrocatalysts, electrolytes, and the electrolytic cell can be sources of nitrogen in the ammonia. Therefore, the 15 N isotope labeling experiment using Na 15 NO 3 as the feedstock is commonly used to confirm the source of nitrogen in ammonia. The typical double peaks of 15 NH 4 + and triple peaks of 14 NH 4 + can be seen via the 1 H nuclear magnetic resonance (NMR) spectroscopy (Figure 4a).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, electrocatalysts, electrolytes, and the electrolytic cell can be sources of nitrogen in the ammonia. Therefore, the 15 N isotope labeling experiment using Na 15 NO 3 as the feedstock is commonly used to confirm the source of nitrogen in ammonia. The typical double peaks of 15 NH 4 + and triple peaks of 14 NH 4 + can be seen via the 1 H nuclear magnetic resonance (NMR) spectroscopy (Figure 4a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, the 15 N isotope labeling experiment using Na 15 NO 3 as the feedstock is commonly used to confirm the source of nitrogen in ammonia. The typical double peaks of 15 NH 4 + and triple peaks of 14 NH 4 + can be seen via the 1 H nuclear magnetic resonance (NMR) spectroscopy (Figure 4a). 49 This result shows that the nitrogen in the ammonia comes entirely from nitrates.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral dust, accounting for 4% of atmospheric particulate matter by mass, , provides important active reaction surfaces for atmospheric heterogeneous reactions. ,, Mineral dust is composed of many metallic oxides, including approximately 10–15% Al 2 O 3 , small fractions of Fe 2 O 3 , MgO, and tiny amounts of TiO 2 . ,, The uptake and oxidation of NOx on the surface of mineral oxides results in the formation of surface nitrate . Nitrate is usually mixed with mineral oxides in the atmosphere. , Therefore, the surface of mineral oxides is an essential and considerable interface for nitrate photolysis. ,, The properties of mineral oxides and the coordination of nitrate with mineral oxides play significant roles in the photochemical reactivity of adsorbed nitrate. ,,, For example, several studies suggest that remarkable NOx production and nitrate consumption takes place on the surface of alumina under irradiation, , while TiO 2 , a kind of semiconductor metal oxide, can provide photogenerated holes and electrons to activate the photolysis of absorbed nitrate, producing more NOx than the nonphotoactive metal oxides. , Besides, the different binding modes of nitrate absorbed on mineral oxides lead to differences in the photolysis rate and the distribution of photolysis products . Wang et al reported that monodentate nitrate (m-NO 3 – ) can be more easily decomposed into NOx than bidentate nitrate (b-NO 3 – ) on the surface of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…24,30,44 The properties of mineral oxides and the coordination of nitrate with mineral oxides play significant roles in the photochemical reactivity of adsorbed nitrate. 24,29,30,44 For example, several studies suggest that remarkable NOx production and nitrate consumption takes place on the surface of alumina under irradiation, 30,45 while TiO 2 , a kind of semiconductor metal oxide, can provide photogenerated holes and electrons to activate the photolysis of absorbed nitrate, producing more NOx than the nonphotoactive metal oxides. 17,30 Besides, the different binding modes of nitrate absorbed on mineral oxides lead to differences in the photolysis rate and the distribution of photolysis products.…”
Section: ■ Introductionmentioning
confidence: 99%